Field education and popular education: there are approaches? / A educação do campo e a educação popular: há aproximações? - Maria Aparecida Vieira de Melo (Universidade Estadual de Alagoas, 2019)
This article came from interest in identifying as it has the pedagogical practice of educators in the field through the opposing ideas of education and popular education. Currently the education field has been re-signified in its political, cultural and economic context, therefore, it is important to talk about, adding the need emerging from a closer discussion with the popular education. As well as scholars of the countryside think education field? This interest, the methodology developed from a bibliographical research about the field of education, popular education and teaching practice. To this end it was possible to understand how researchers think about the context of the field and its specificities. The light of some researchers as Arroyo (2005); Molina (2006); Caldart (2002); Wanderley (2010) and others were possible confront the empirical context with the possibilities advocated by the authors as methodological alternatives that support for the process of learning, appreciation of culture, identity and context in which it develops the education field. The rural education and popular education have theoretically approached, which are relevant in order to develop actually in the schools of the field, which many of them have a traditional practice, merely urbanocêntrica.